Use of Pluronic Surfactants in Gel Formulations of Photosensitive 1,4-Dihydropyridine Derivatives: A Potential Approach in the Treatment of Neuropathic Pain - Giuseppina Ioele; Rita Muzzalupo; Miyase Gözde Gündüz; Michele De Luca; Elisabetta Mazzotta; Fedora Grande; Maria Antonietta Occhiuzzi; Antonio Garofalo; Gaetano Ragno (MDPI AG, 2021)
1,4-Dihydropyridines (DHPs) are the most important class of L-type calcium channel blockers that are employed for the treatment of cardiovascular diseases, particularly hypertension. Various modifications on this scaffold lead to the discovery of new DHPs blocking different types of calcium channels. Among them, the T-type calcium channel has recently attracted great interest due to its role in chronic pain conditions. In this study, we selected three newly synthesized DHPs (HM8, HM10 and MD20) with different selectivity profiles to the T-type calcium channel and formulated them in micellar solutions and micellar-in-gel matrices to be tested for potential topical use in the treatment of neuropathic pain. To prevent the well-known sensitivity to light of the DHPs, the studied compounds were entrapped in colloidal aggregates obtained by using edible Pluronic® surfactants and adding α-tocopherol as an antioxidant. All the prepared formulations were exposed to stressing light, according to international rules. Along with the degradation experiments, the concentrations of the parent compounds and by-products were calculated by multivariate curve resolution-alternating least squares (MCR-ALS) applied to the spectral data. The defined formulations proved suitable as light-stable matrices for the DHP compounds, showing an increase in stability for HM8 and MD20 and an almost complete photoprotection for HM10, compared to ethanol solutions and standard gel formulations.